Mengungkapkan Tata Kelola Dana Punia Pura Berbasis Teknologi Digital: Studi Pada Pura Tanah Kilap Denpasar - Kadek Ely Shima Parwati; I Made Endra Lesmana Putra; Ni Putu Ayu Kusumawati (UNHI Press, 2026)
The temples as religious and social institutions in Bali, play a crucial role in managing congregational funds sourced from punia funds, community dues, and voluntary donations. Conventional financial management has the potential to create accountability, transparency, and efficiency issues. With the advancement of digital technology, there is an opportunity to improve temple financial governance through a more structured and transparent recording and reporting system. This study aims to explore in-depth temple financial governance practices and the adoption of digital technology in financial management at Tanah Kilap Temple in Denpasar. The study employed a qualitative approach, collecting data through in-depth interviews, observation, and documentation with temple administrators and related parties. The results indicate that digitalizing financial management has the potential to improve recording accuracy, reporting transparency, and congregational trust. However, its implementation still faces challenges such as limited human resources, infrastructure readiness, and adaptation to conventional work cultures. This research is expected to provide conceptual and practical contributions to the development of accountable, digital-based temple financial governance, particularly in Hindu religious institutions in Bali.